2019
DOI: 10.1075/gest.00034.gaw
|View full text |Cite
|
Sign up to set email alerts
|

Data transparency and citation in the journal Gesture

Abstract: Data is central to scholarly research, but the nature and location of data used is often under-reported in research publications. Greater transparency and citation of data have positive effects for the culture of research. This article presents the results of a survey of data citation in six years of articles published in the journal Gesture (12.1–17.2). Gesture researchers draw on a broad range of data types, but the source and location of data are often not disclosed in publications. There is also still a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In future research it would be useful to examine whether the superiority of specific pointing gestures (i.e., deictic gestures) remains for other kinds of onscreen agents and when compared against a natural combination of beat, iconic, and metaphorical gesturing as well as each type separately. Researchers have isolated three other types of gestures beyond pointing gestures that are often used in human communication, for example, iconic gestures (i.e., referring to concrete objects), metaphoric gestures (i.e., referring to abstract concepts), and beat gestures (i.e., used to show emphasis; Gawne et al, 2009). Future study can explore the role of these three other gestures in learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future research it would be useful to examine whether the superiority of specific pointing gestures (i.e., deictic gestures) remains for other kinds of onscreen agents and when compared against a natural combination of beat, iconic, and metaphorical gesturing as well as each type separately. Researchers have isolated three other types of gestures beyond pointing gestures that are often used in human communication, for example, iconic gestures (i.e., referring to concrete objects), metaphoric gestures (i.e., referring to abstract concepts), and beat gestures (i.e., used to show emphasis; Gawne et al, 2009). Future study can explore the role of these three other gestures in learning.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the pedagogical agents exhibited specific pointing gestures toward the task-related element on a graphic with their hand, eye gaze, and/or body rotation when the narration referred to it (Baylor & Kim, 2009; Johnson, Ozogul, Moreno, & Reisslein, 2013; Johnson, Ozogul, & Reisslein, 2015; Moreno, Reislein, & Ozogul, 2010; Twyford & Craig, 2013; Wang et al, 2018); in other studies, the pedagogical agents exhibited general gestures that guided learners to look in the direction of the presentation using their hand, eye gaze, and/or body rotation (Craig et al, 2002; Dunsworth & Atkinson, 2007; Lusk & Atkinson, 2007; Mayer & DaPra, 2012; Yung & Paas, 2015); in yet other studies, pedagogical engaged in casual NPGs without any specific visual guidance (Baylor & Ryu, 2003; Beege, Schneider, Nebel, & Rey, 2017; Shiban et al, 2015). Considering that different kinds of gestures may have different influence on learning (Gawne, Kelly, & Unger, 2009; Hostetter, 2011) and majority of previous studies are vague in the descriptions of the gestures displayed by pedagogical agents, it is worthwhile to disentangle the effects of different kinds of pedagogical agent gestures on instructional effectiveness in multimedia learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This sharing, in turn, can contribute to advancing subfields of linguistics more efficiently and in a collaborative effort (Gawne et al, 2017). Nowadays, publicly sharing research materials can be achieved by a few mouse clicks if these resources are not restricted for sharing, e.g., due to copyright.…”
Section: Materials Sharingmentioning
confidence: 99%
“…Assessments of second language research Plonsky et al, 2015) reported limited sharing of materials (4-17%) and data (15%), and bilingualism researchers suggest poor availability of data, analysis, and materials in their subfield (Bolibaugh et al, 2021). An assessment of a language documentation and description subfield also concluded that methodology and data collection practices were not explicitly reported or shared in grammars and dissertations published between 2003 and 2012 (Gawne et al, 2017). A more recent assessment which targeted a specific psycholinguistic journal reported 12-20% of articles sharing data and code before an open data mandate was introduced (Laurinavichyute et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Due to this lack of technical solutions, it is still common in research on multimodal communication and other kinematic research areas to forgo sharing the original video recordings (e.g., [6]) or to conditionally share them upon request as often required by journal policies [7,8]. Unfortunately, researchers seldom ratify sharing requests, as previous research shows [9].…”
Section: Introductionmentioning
confidence: 99%